Pilgrimage to Broken Mountain: Nahua sacred journeys in Mexico's Huasteca Veracruzana - Sandstrom, Alan R. (University Press of Colorado, 2022)
"Based on decades of research, Pilgrimage to Broken Mountain explores journeys to the mountains undertaken by Nahua people in northern Veracruz. Providing descriptions and analysis of these journeys punctuated with offerings dedicated to the forces responsible for natural phenomena, the work documents journeys for the Nahua generation living in a global world"--